Avaliação da influência da temperatura em proteínas vegetais - Falkowski, David Junior (2023)
Although most of the proteins present in the human diet are obtained from animal sources, there is a growing interest in plant-based proteins. Among the motivations for increasing consumption of plant-based proteins are concerns about the environment, such as water usage, the allocation of land for growing animal feed, and the impacts of climate change, along with animal welfare concerns. Proteins have been applied in various food formulations, many of which involve heating processes, such as in the case of bread, cakes, and cookies. This study aimed to evaluate the influence of heating on plant-based proteins in powder form by applying different temperatures and exposure times. The results were obtained using near-infrared spectroscopy, and the multivariate curve resolution method with alternating least squares (MCR-ALS) was applied to interpret the data. Pea, pumpkin seed, rice, soy, and cannabis proteins were evaluated, each measured in 9 replicates. Spectra were obtained immediately after opening the protein packaging and after heating at 35, 50, 100, 150, 160, 170, and 180 °C using an air-circulating oven for homogeneous sample heating. The samples were exposed to each of these temperatures for exposure times of 20, 40, and 60 minutes. With the spectral variations observed after different heatings, the results indicate different structural transformations in the proteins (different folding) depending on the source (type). Thus, from the data recovered by MCR-ALS, rice proteins were the most resistant to heating, while pea proteins were the most susceptible to temperature-related changes.